Режими течії двофазових сумішей у проточному барботажному шарі утилізатора теплоти відхідних газів - Костюк, О. П. (НТУ "ХПІ", 2014)
Статтю присвячено експериментальним дослідженням, що направлені на підвищення ефективності роботи контактних тепломасообмінних апаратів шляхом збільшення міжфазної поверхні теплообміну та швидкості руху фаз. В роботі представлені результати експериментальних досліджень гідродинамічних режимів та форм руху газорідинних сумішей у проточному двофазовому шарі утилізатора теплоти відхідних газів, визначені межі стійкого двофазового режиму, що відповідають граничним значенням критерію стійкості двофазового потоку (критерію Кутателадзе) та безрозмірної швидкості рідини (критерію Фруда).

This paper is devoted to the research done to increase the operation efficiency of contact units through an increase of the interphase heat-exchange surface and the rate of motion of the phases. The problem related to the cooling of steam -gas mixture in the flow bubbling layer (a dynamic two-phase layer with the rates of light and heavy phases that are not equal to zero) is very vital for high-efficiency contact heat utilizers of released gases emitted by different power supply units. The studies of the processes that occur in the system under the consideration include. Hydrodynamic studies, in particular with regard to the bubbling mode in the vertical pipes of a small diameter were limited to the studies of the flow structure and parameters in the sections of a considerable height. The attention was not paid to the region in the vicinity of the phase mixer, which is responsible for the transfer of a considerable amount of heat and mass. This scientific paper gives the results of experimental research of hydrodynamic modes and the motion forms of gas liquid mixtures in the flow two-phase balloon of the heat utilizer of released gases. It also determines the boundaries of the stable two-phase mode, which correspond to the ultimate values of the stability criterion of the two-phase flow (Kutateladze criterion) and dimensionless liquid velocity (Froude criterion).
Flow modes of two-phase mixtures in the flow bubbling balloon of the heat-utilizer of released gases
Keywords: газорідинна суміш; проточний барботажний шар; контактний тепломасообмінний апарат; вертикальний канал; nitrogen liquid mixture; cocurrent flow; two-phase flow; flow bubbling layer; contact-type heat-exchange unit; vertical channel